Distinction of naive and memory BoCD4 lymphocytes in calves with a monoclonal antibody, CC76, to a restricted determinant of the bovine leukocyte-common antigen, CD45 - Howard, C.J.; Sopp, P.; Parsons, K.R.; McKeever, Declan J.; Taracha, E.L.N.; Jones, B.V.; MacHugh, Niall D.; Morrison, W. Ivan (Wiley, 1991)
A murine IgG1 monoclonal antibody (mAb), CC76, has been produced that, based on findings of the relative molecular mass of polypeptides that it recognized, staining of leukocytes in blood and tissues, and the biological properties of the T lymphocyte subpopulations with which it reacts, is considered to identify an isoform of the leukocyte common antigen (LCA) family of molecules in cattle. The mAb is more similar to human CD45R which detect products requiring the presence of the B exon within the LCA gene and to the anti‐rat mAb MRC‐OX22, than to CD45RA or CD45RO. mAb CC76 reacts with an antigen expressed by subpopulations of cells in bovine blood that express BoCD2 and either the BoCD4 or BoCD8 antigens. T cells that express the γ/δ T cell receptor identified with mAb to BoWC1 antigen did not react with CC76. The molecule detected is expressed on B cells but not on monocytes or granulocytes. Only 2% of cells in thymic suspensions stained with mAb CC76. Immature cortical thymocytes that were BoCD1+ did not react with CC76 and 90% of the cells in thymic suspensions that were CC76+ had the phenotype of mature thymocytes. These cells were primarily in the medulla. The LCA isoform detected thus appears to be acquired by mature cells shortly before emigration from the thymic medulla into the periphery. Expression of the molecule detected by mAb CC76 on cells from lymph nodes was similar to that in blood, but expression on cells from the gut mucosa was quite different. Almost all, 95% and 93% respectively, of the BoCD4+ cells in the gut mucosa or discrete Peyer's patches were CC76−. A greater proportion of BoCD8+ cells from these sites, 35% and 26%, expressed the antigen.Lymphocytes from animals that had been immunized with Trypanosoma brucei were sorted into BoCD4+, CC76+ and BoCD4+, CC76− populations and cultured in vitro with the variable surface glycoprotein antigen from the parasite. Lymphocyte transformation responses were entirely within the CC76− population indicating that the mAb distinguished naive from memory BoCD4+ T cells in cattle. Major histocompatibility complex (MHC) class I‐restricted cytotoxic precursor cells that expressed the BoCD8 antigen sorted from cattle that were immune to Theileria parva were both CC76+ and CC76− indicating that different isoforms of the LCA may be expressed on MHC class 1‐ and class II‐restricted memory cells and that BoCDS memory cells are heterogeneous with respect to the LCA isoform that they express.